Mongolia social protection sector fact sheet. (Asian Development Bank, 2017)
Due to persistent economic volatility, limited diversification, internal migration, and rapid urbanization, Mongolia currently faces rising inequality, expanding informal sector employment, and increasing vulnerability. This requires continuous focus on further improving the country social protection and welfare system. Through a mixture of programs, projects and technical assistance (TA) the bank has helped Mongolia mitigate the adverse impacts of economic crises, ensure fiscal sustainability, develop welfare systems, and improve social protection services and service delivery.